Brain-derived neurotrophic factor in substance use disorders: A systematic review and meta-analysis. (1st December 2018) - Ornell, Felipe; Hansen, Fernanda; Schuch, Felipe Barreto; Pezzini Rebelatto, Fernando; Tavares, Ana Laura; Scherer, Juliana Nichterwitz; Valerio, Andrei Garziera; Pechansky, Flavio; Paim Kessler, Felix Henrique; von Diemen, Lisia
Highlights: Patients with active drug use show lower serum brain-derived neurotropic factor (BDNF) than controls. There is no difference between BDNF levels of abstinence users and controls. Alcohol and crack/cocaine users showed lower levels of serum BDNF than controls. Sex, age, and age of the first use influence BDNF levels in subjects with substance use disorders (SUDs). Abstract: Background: Brain-derived neurotrophic factor (BDNF) is associated with several neurodegenerative and psychiatric disorders. It is not clear, however, whether BDNF levels are modified in substance use disorders (SUDs). Methods: We conducted a systematic search of electronic databases to identify studies comparing peripheral plasma or serum BDNF levels in adults with SUDs vs. non-user controls. Forty studies were included in the meta-analysis involving a total of 2238 participants with SUDs and 2574 controls. Results: After trim and fill adjustment, current drug users presented lower serum BDNF levels (SMD = −0.99, 95%CI −1.40 to −0.58, I 2 = 95.9) than non-user controls. However, this difference disappears during withdrawal. Studies using serum or plasma BDNF samples have shown different results. Subgroup analysis revealed lower levels of serum BDNF in alcohol users (SMD = −0.70, 95%CI −1.15 to −0.25, I 2 = 89.81) and crack/cocaine users (SMD = −1.78, 95%CI −2.92 to −0.65, I 2 = 97.59) than controls. Meta-regression analysis revealed that gender, age, and age of first use moderate the effects of drug use in peripheral BDNF levels. Conclusions: Peripheral BDNF levels are decreased in the serum, but not the plasma, of active drug users. Altogether, these findings suggest that BDNF levels may be related to acute use and addiction severity and also point to BDNF's potential utility as a biomarker in this population.